Partnership and Collaboration System to Increase Creative Industry Sales Tangan Di Atas (TDA) Community of Semarang City - Margunani, Margunani; Hidayah, Isti; Ardiansari, Anindya; Apriyanti, Rita; Rachmadi, Moch Faizal (Universitas Negeri Semarang, 2023)
Tangan Di Atas (TDA) is a community of young entrepreneurs in Indonesia and spread across various regions, one of which is Semarang City. There are various business fields in the TDA Community of Semarang City such as culinary, fashion and so on, including the creative industry sector. The development of the creative industry presents its own challenges for every individual, namely becoming a producer who is always thinking about creating creative and innovative products. However, there are several obstacles faced, such as 1) Not having knowledge about the importance of partnerships and collaboration; 2) There is no cooperation in running a creative industry business; and 3) The TDA community network is not yet optimal as a medium for collaboration between entrepreneurs. The method used in this service is to carry out socialization as the first stage, then continue with providing comprehensive, integrated and sustainable training. After that, the service team facilitates efforts to increase sales of creative products through business camps, coaching clinics, product promotions and so on. After that, intensive and continuous assistance is carried out. After carrying out this service activity, creative industry players, especially the TDA Community of Semarang City, can intensify and optimize partnership systems, integrated collaboration and other business development efforts.